Analysing maintenance strategies by FANP considering RAM criteria: a case study. Issue 3 (1st January 2014) - Pourjavad, Ehsan; Shirouyehzad, Hadi
Adopting the most suitable maintenance strategy is one of the main challenges that maintenance managers face. The main purpose of this paper is to propose a new approach to evaluate maintenance strategies. In this study, three criteria called reliability, availability and maintainability (RAM) have been employed to compare maintenance strategies. Considering interactive effects of criteria and alternatives and interdependence of criteria, the analytic network process (ANP) is suitable for comparison. Furthermore, in some cases, due to the ambiguity and uncertainty on the judgements of a decision-maker, the crisp pair-wise comparison in the formal ANP is inadequate and imprecise to capture the right judgements of the decision maker. Therefore, a fuzzy logic is presented in the pair-wise comparison of ANP to make up for this shortage in the formal ANP, and is called as fuzzy ANP. In short, in this paper, a fuzzy ANP-based approach is proposed to evaluate maintenance strategies. The proposed method has been employed to evaluate maintenance strategies for one category of equipments in Chadormalu Mining-Industry Company, according to three RAM criteria. CBM has been selected as the most suitable strategy.